Hydrophobic pillared square grids for selective removal of CO2 from simulated flue gas. Issue 85 (8th September 2015) - Elsaidi, Sameh K.; Mohamed, Mona H.; Schaef, Herbert T.; Kumar, Amrit; Lusi, Matteo; Pham, Tony; Forrest, Katherine A.; Space, Brian; Xu, Wenqian; Halder, Gregory J.; Liu, Jun; Zaworotko, Michael J.; et al.
Abstract : Capture of CO2 from flue gas is considered to be a feasible approach to mitigate the effects of anthropogenic emission of CO2 . Abstract : Capture of CO2 from flue gas is considered to be a feasible approach to mitigate the effects of anthropogenic emission of CO2 . Herein we report that an isostructural family of metal organic materials (MOMs) of general formula [M(linker)2(pillar)], linker = pyrazine, pillar = hexaflourosilicate and M = Zn, Cu, Ni and Co exhibits highly selective removal of CO2 from dry and wet simulated flue gas. Two members of the family, M = Ni and Co, SIFSIX-3-Ni and SIFSIX-3-Co, respectively, are reported for the first time and compared with the previously reported Zn and Cu analogs.